# algebraic expression

Views:

Category: Education

## Presentation Description

No description available.

## Presentation Transcript

### Slide 1:

Write a number Write an expression

### Slide 2:

Rectangle Perimeter of the rectangle = 4 + 3 + 4 + 3 = 14 cm 4 cm 3 cm 3 cm 4 cm

### Slide 3:

Perimeter of the rectangle = 2 x + x + 2 x + x = 6 x 2 x cm x cm x cm 2 x cm expression

### Slide 4:

4 cm x cm Perimeter of the rectangle = 4 + x + 4 + x = 8 + 2 x x cm 4 cm Linear expression

### Slide 5:

Perimeter of the rectangle = ( x+3) + x + ( x+3) + x = x+3 + x + x+3 + x = 6 + 4 x (x +3) cm x cm x cm (x+3) cm

### Slide 6:

Rectangle 4 cm 3 cm Area of the rectangle = (4)(3) = 12 cm 2

### Slide 7:

4 cm x cm Area of the rectangle = (4)( x ) = 4 x expression

### Slide 8:

3 x cm x cm Area of the rectangle = (3 x )( x ) = 3 x 2 Quadratic expression

### Slide 9:

( x + 3) cm x cm Area of the rectangle = ( x + 3)( x ) = x ( x + 3) Role Play “memberi salam” = ( )( ) + ( )( ) = ( x )( x ) + ( x )(+3) = x 2 + 3 x

### Slide 10:

( x + 3) cm (x+2) cm Area of the rectangle = ( x + 3)( x + 2 ) = x ( x + 2) + 3( x + 2) =( )( ) +( )( )+( )( )+( )( ) = x 2 + 2 x + 3 x + 6 = x 2 + 5 x + 6 =( x )( x ) +(x)(+2) +(3)( x ) +(3)(+2)

### Slide 11:

( x + 3) cm (x-2) cm Area of the rectangle = ( x + 3)( x - 2 ) = x ( x - 2) + 3( x - 2) =( )( ) +( )( )+( )( )+( )( ) = x 2 - 2 x + 3 x - 6 = x 2 + 1 x - 6 =( x )( x ) +(x)(-2) +(3)( x ) +(3)(-2)

### Slide 12:

( x - 3) cm (x-2) cm Area of the rectangle = ( x - 3)( x - 2 ) = x ( x - 2) - 3( x - 2) =( )( ) +( )( )+( )( )+( )( ) = x 2 - 2 x - 3 x + 6 = x 2 - 5 x + 6 =( x )( x ) +(x)(-2) +(-3)( x ) +(-3)(-2)

### Slide 13:

Po po po Po ne ne Ne po ne Ne ne po (+)(+) = (+) (+)(-) = (-) (-)(+) = (-) (-)(-) = (+)

### Slide 14:

=( )( ) +( )( )+( )( )+( )( ) Alternative way of salam = x 2 +1 x - 4 x - 4 = x 2 - 3 x - 4 =( x )( x ) +(x)(+1) +(-4)( x ) +(-4)(+1)

### Slide 15:

=( )( ) +( )( )+( )( )+( )( ) Alternative way of salam = x 2 - 4 - 4 x + 1 x = x 2 - 3 x - 4 =( x )( x ) +(-4)(+1) +(-4)( x ) +( x )(+1)